1997
DOI: 10.1079/bjn19970115
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses to isoenergetic meals containing different proportions of carbohydrate and fat

Abstract: The purpose of the present study was to investigate the interrelationship between carbohydrate and fat metabolism at rest after isoenergetic meals of varying proportions of carbohydrate and fat. Eight physically-active subjects (BMI 18.1-23-4 kg/m2) were studied at rest on three occasions after an overnight fast. In a balanced design they were given meals containing carbohydrate, protein and fat in the following amounts respectively (g/70 kg body weight): meal 1 121,16,48; meal 2 70,16,70; meal 3 50, 14, 80. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 23 publications
7
19
1
Order By: Relevance
“…Previous studies, performed in healthy individuals, have shown opposite results for an acute fat load with regard to its effect on REE and fat oxidation [11,17,28]. In line with other investigations [6,29], no significant difference in the basal fat oxidation was demonstrated between individuals with vs. without hepatic fat accumulation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies, performed in healthy individuals, have shown opposite results for an acute fat load with regard to its effect on REE and fat oxidation [11,17,28]. In line with other investigations [6,29], no significant difference in the basal fat oxidation was demonstrated between individuals with vs. without hepatic fat accumulation.…”
Section: Discussionsupporting
confidence: 78%
“…The fat load consisted of 190 grams of a commercially available fresh cream (343 kcal/100 g; calories from fats, carbohydrates and proteins were 84% [17], 13% and 3% respectively; 70% saturated fatty acid, 0% cholesterol). The amount of the fresh cream (a dose equivalent to three full glasses) was chosen on the base of results of a previous investigation [3], taking into account the compliance of the participants to consume this food, assessed before the start of the study (190 g providing 652 kcal and containing 61 g of fats).…”
Section: Oral Fat Loading Testmentioning
confidence: 99%
“…By coincidence, our own study with an extremely similar design has also just been published (Whitley et al, 1997) and reaches almost identical conclusions. These studies show that there are intimate relationships between carbohydrate and fat oxidation after isoenergetic meals, such that the sum of their contribution to energy expenditure remains virtually identical, but the ratio varies according to the composition of the meal administered.…”
supporting
confidence: 71%
“…Since shift workers have increased risk of becoming obese [112], the impact of their food preference certainly requires investigation. During short-term (one to seven days) food intervention studies, healthy subjects have been able to adjust their macronutrient oxidation to the composition of isocaloric diets in most studies [3,15,68,91,97,99,129], whereas other studies have not found that fat oxidation correlates with fat intake [92,103]. The main reason for the divergent opinions regarding the high-fat diets role in the development of obesity is failure to take energy density into consideration.…”
Section: Dietmentioning
confidence: 95%